METHODOLOGY FOR DEVELOPING STUDENTS’ MEDICAL-TECHNICAL KNOWLEDGE THROUGH INNOVATIVE TECHNOLOGIES IN ENGLISH LANGUAGE CLASSES - Hamroyeva Sanobar Hasan qizi (International Journal of Literature and Language Studies, 2026)
. This article presents a methodology for effectively introducing students to medical-technical knowledge in English language classes and developing this knowledge through innovative pedagogical technologies. The proposed approach involves the integration of module-based interactive lessons, virtual laboratories, simulations, and distance learning tools. The methodology coordinates the acquisition of professional terminology, the development of practical skills, and the solution of medical-technical problems through communicative tasks. In the experimental study, students’ understanding of terminology, practical competence, and motivation were assessed; the obtained results demonstrated the potential of the methodology to improve educational effectiveness and ensure safe, realistic learning activities. The article provides practical recommendations for incorporating virtual modules and simulations into curricula and for improving teachers’ professional competence.